Analisa Faktor Eksternal dan Perencanaan Keuangan PT ESP dalam Pemanfaatkan Tandan Kosong Kelapa Sawit Sebagai Alternatif Bahan Bakar Terbarukan - Sunarsih, Fatimah; Hamdi, Edi; Iskandar, Muhammad; Negoro, Dimas (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
Financial projections in business are written plans that contain the business to be managed, the vision and mission of the business, entrepreneurs with their businesses and the methods or strategies that will be carried out to achieve the goals that have been set. Forecasting and estimating financial reports are used to see the company's survival in terms of its performance and financial position. The purpose of this service is to create a financial projection of a business plan in seeing the feasibility by comparing revenue and cost projections as determinants of the feasibility of a business. This study explores the technical and economic feasibility of utilizing TKKS waste from the palm oil industry for energy production. The use of TKKS pellets has proven to be more efficient in terms of cost and provides significant environmental benefits, including reducing greenhouse gas emissions compared to the use of conventional coal. In addition, this project supports Indonesia's renewable energy targets and encourages sustainable waste management practices in the palm oil sector. This study also raises the potential for implementing circular economy principles by converting industrial waste into valuable energy sources. Recommendations include optimizing the supply chain and developing pellet production technology to increase efficiency and ensure the long-term sustainability of this project.